Trends in Historical Writing Jordan during the First Centennial of the Jordanian State: An Analytical Study of Research Methods and Content - Mahafzah, Ali Mofleh; alrawadieh, Almahdi (Jordan Journal for History and Archaeology, 2022)
This article focuses on the beginning of interest in historical writing on Jordan as well as on the political trends of those writings about the modern history of Jordan: the official trend, the exaggerated loyalist trend and the political opposition trend. The article also examines the Arab historical writings on Jordan according to research methodology, throughout the ancient, Islamic, Ottoman and modern periods. Their scientific and methodological orientations as well as the authors’ remarks on those writings are included.